A. - 7x² + 7x + 1 + 8 = 0
- 7x² + 7x + 9 = 0
x = - b ± √b² - 4ac / 2a
= - 7 ± √7² - 4 (-7) (9) / 2 (-7)
= - 7 ± √49 + 252 / - 14
= - 7 ± √ 301 / - 14
x = - 7 + 17.349 / - 14 x = - 7 - 17.349 / - 14
= 10.349 / - 14 = - 24.349 / - 14
= - 0.739 = - 1.739
B. 8x² - 5x² + 6x + 1 = 0
3x² + 6x + 1 = 0
x = - b ± √b² - 4ac / 2a
= - (-5) ± √-5² - 4 (3) (1) / 2 (3)
= 5 ± √25 - 12 / 6
= 5 ± √ 13 / 6
x = 5 + 3.606 /6 x = - 5 - 3.606 / 6
= 8.606/6 = - 8.606/6
= 1.434. = - 1.434
please re-check the answers hope this helps